The Correlation between Teacher’s Immediacy and Junior High School Students Willingness to Communicate in English in the Classroom - Nauvall, Abyan; Areni, Galuh Kirana Dwi (Journal of English Language and Education, 2025)
This study investigates the correlation between teacher immediacy and junior high school students’ willingness to communicate (WTC) in English during classroom interactions. Teacher immediacy refers to verbal and non-verbal behaviors that reduce the psychological distance between teachers and students, such as smiling, using students' names, providing encouragement, and maintaining eye contact. These behaviors are categorized into instructional and relational immediacy. Conducted at SMPN 23 Semarang, the research involved 32 eighth-grade students and employed a quantitative correlational method using Likert-scale questionnaires adapted from Zhang Oetzel (2006) for teacher immediacy and Gol et al. (2014) for WTC. The study aimed to determine whether a significant correlation exists between perceived teacher immediacy and students’ WTC in English. Statistical analysis using SPSS 26 revealed a Pearson correlation coefficient of 0.378 with a significance value of 0.033, indicating a moderate and statistically significant positive relationship between the variables. The findings suggest that students who perceive higher levels of teacher immediacy tend to exhibit a greater willingness to engage in English communication during class. Among the immediacy aspects, students perceived the teacher’s commitment to teaching and encouragement as the most prominent behaviors that foster communication. This study highlights the crucial role of teacher-student interpersonal dynamics in shaping communicative engagement and recommends that English teachers at the junior high school level consciously develop immediacy behaviors to create a more supportive and communicative classroom environment.